The basis of the principle of self-sufficiency of commercial paper (Analytical study) - Ahmed Naeem, Researcher. Mansour; Omar Mohammed, Prof.Dr. Alaa (Basra studies journal, 2025)
In the context of the search for the principle of self-sufficiency of commercial paper, one can find that there is a lack of finding a logical explanation of this principle. So the research for a technical tool can bring the greatest stability to the parties of the legal relationship, taking into account the interest of the third party who is related to the legal relationship in good faith, without realizing the flaws of the will of the parties . The end of the research was directed to the idea of abstraction as the achievement of the greatest stability in the circle of legal acts . In fact, the principle of self-sufficiency of a commercial paper is completely dependent on the property of abstraction in proving its effectiveness, since dealing with commercial papers is far from the basic relationship that the paper was issued to achieve, and the paper's self-sufficiency has the strongest effect on the holder's relationship with the previous signatories to the paper in terms of the irreversibility of the basic relationship on the basis of which the commercial paper was issued.